Synthesis and Insecticidal Studies of Hydroxytriazenes - Rezaie, Behrooz; Ressalan, S.; Chauhan, R.S.; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
Synthesis of 3-hydroxy-3-p-tolyl-1-m-chelorophenyltriazene has been done and its insecticidal activity against Drosophila melanogaster meig has been studied. The LC50 values are 1.50 ppm which are quite encouraging.